Development of a headspace-gas chromatography/mass spectrometry method based on matrix-matched calibration for evaluating VOC content, characterization, source, and risk in RO membrane. (March 2022) - Hou, Mingtao; Ren, Huixue; Cheng, Wenqing; Li, Lingjie; Zhang, Shuai; Chen, Yanxue; Yu, Chunfeng; Li, Fangjun; Tian, Shuying; Deng, Zhe
Abstract: Analytical method has been developed to determine volatile organic compounds (VOCs) in reverse osmosis (RO) membrane using headspace-gas chromatography/mass spectrometry (HS-GC/MS). The operating parameters, including incubation temperature, incubation time and the choice of matrix modifier, were investigated. The existence of matrix effect was evaluated and the VOC-free RO membrane was selected as the best material for developing matrix-matched calibration curve. At these optimized operating conditions, the established method was found to perform well — giving good linearity ( r  > 0.996), allowing for consistent repeatability (<9.5%), making possible high levels of VOC recoveries (84.7%–123%) and satisfactory detection limits (3.44–748 μg/kg). The method was applied to determining thirty-seven common VOCs for RO membrane. Toluene and N, N -dimethylformamide were the most abundant VOCs in measured samples, with average contents of 90 087 μg/kg and 249 957 μg/kg respectively. In addition, a range of other common compounds, including acetone, dichloromethane, hexane, chloroform, 1, 2-dichloroethane, benzene, chlorobenzene, ethylbenzene, xylene, and styrene, were also found with content between N.D.—112 419 μg/kg in detection rate between 40%–100%. The analysis of VOC distribution provides further substantial evidence that the solvents used during the production of the RO membrane frequently are the main source of VOCs in commercial RO membrane. Our experiments proved that, of these VOCs, four compounds, dichloromethane, chloroform, 1, 2-dichloroethane, and toluene, were hardly removed by pre-washing. The relationship between the content of VOCs in RO membrane and their corresponding concentration in filtrated water shows a highly positive correlation and the safety limit values for these four compounds are evaluated as 2.6 × 10 2 –3.8 × 10 5  μg/kg, but more accurate and completed guideline values should be formulated to guarantee the RO membrane quality. Highlights: Headspace technology was employed as an effective pretreatment method for VOC determination in RO membranes. The results obtained via matrix-matched calibration was easy, accurate and cost-effective. Source and potential risk assessment of VOCs in RO membranes were discussed in this paper.